PROSES PENGENDAPAN DAN LINGKUNGAN PENGENDAPAN SERPIH FORMASI NANGGULAN, KULON PROGO, YOGYAKARTA BERDASARKAN DATA BATUAN INTI - Ahmad Z Al Ansori, Ahmad Z Al Ansori (Jurusan Teknik Geologi, 2014)
Indonesia is one country that has big potential of shale gas. Most source rock in the western Indonesia which acts as a potential target of shale gas exploration is synrift sediments Eocene to Oligocene shale. Nanggulan Formation which exposed in Kulon Progo, Yogyakarta is one of the Eocene shale interval known. However, the data about it is still limited. Further studies on the Nanggulan Formation in Kulon Progo is necessary to know depositional process and depositional environment of the Eocene shale more detail. This research uses lithofacies and lithofacies association analysis from core data. Succession of lithofacies Nanggulan shale, Kulon Progo, Yogyakarta based on core data consists of 1. Laminated sandstone facies, 2. Massive sandstone facies, 3. Flaser-Wavy sandstone facies, 4. Massive claystone facies, 5. Massive mudstone facies, 6. Molusca rich mudstone facies, 7. Floatstone facies, 8. Crystalline carbonate facies, 9. Coal facies, 10. Claystone and sandstone interbedded facies, 11. Lenticular mudstone facies. Depositional environment of Nanggulan Formation starts from fluvial, tidal dominant estuarine to shallow marine. In general, depositional environment is deepening. Deposition process in the fluvial and estuarine influenced by river flow and tidal currents. Deposition process in a shallow marine is hypopycnal flow and hyperpycnal flow. Keywords: Shale Gas, Nanggulan Formation, Lithofacies, Depositional Environment and Depositional Process